Implementation of Sensory Marketing in Korean Concept Hotels - MBULU, Yustisia Pasfatima; KAUSAR, Devi Roza K. (Journal of Environmental Management and Tourism, 2025)
The hospitality industry continues to innovate and renew itself to build a personal and profound brand for hotel guests. The hospitality industry in Indonesia, in particular, continues to grow with various concepts applied to create a different experience. Indonesia is currently heavily influenced by Korean culture, particularly the K-pop phenomenon. Korean dramas, food, fashion, and cosmetics are increasingly popular among young people and are spreading rapidly in Indonesia. So, the influence of Korean culture is also emerging in the hospitality industry. One of the hotels that adopt Korean culture is Tama Boutique Hotel Bandung . This study aims to apply sensory marketing in a Korean concept hotel, a case study of Tama Boutique Hotel Bandung. The method used is the Netnography method. To collect data through reviews from Travelokal, Google.com, and Agoda.com to get answers to the application of sensory marketing in the Korean concept Tama Boutique hotel. In this study, researchers also interviewed informants who had stayed at the Tama Boutique Hotel. I will also conduct direct observations of the Korean concept of the Tama Boutique Hotel in Bandung. The results obtained that the application of sensory marketing on the sense of "sight" at Tama Boutique Hotel with a Korean concept in building a new brand reached 65% seen from the design, lighting, and ornaments that are typical of Korea then the application of sensory marketing on the sense of "hearing" in building a new brand reached 20.5%. The sense of "smell" in building a new brand reached 22.5% because the elements of "hearing" and "smell" have not been applied optimally. Furthermore, according to theory, the application of sensory marketing on the sense of "Taste" in building a brand has reached 31%. In comparison, the sense of "Touch" in creating a new brand reached 12.5% ​​ because its application is still minimal.